Peer review of the pesticide risk assessment for the triazole derivative metabolites in light of confirmatory data submitted. (27th July 2018) - ,; Brancato, Alba; Brocca, Daniela; Carrasco Cabrera, Luis; Chiusolo, Arianna; Civitella, Consuelo; Court Marques, Daniele; Crivellente, Federica; De Lentdecker, Chloe; Erdös, Zoltan; Ferreira, Lucien; Goumenou, Marina; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessment carried out by the competent authority of the rapporteur Member State, the United Kingdom, for the pesticide risk assessment for the triazole derivative metabolites are reported. The context of the peer review was that requested by the European Commission following the submission and evaluation of confirmatory data in relation to mammalian toxicology, metabolism and residue data. The conclusions were reached on the basis of the evaluation of various uses for a number of triazole fungicides. Recommendations are proposed. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.